Kemenangan petahana (incumbent), pada pemilihan kepala daerah 2015; (Strategi Politik dan Marketing Politik Pada Pilwali Kota Surabaya dan Pilbup Kab. Malang) - Khoiron Khoiron (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
Elections are one of the most important components or instruments in a country's political system. As a political system, elections will be a quality democracy party for both the presidential elections at the central and regional or local levels, as long as the political principles and values ​​of ethics and moral integrity are met. In the 2015 election of the Head of Region, there is an interesting political fact that there are many incumbent candidates, who have failed to win, there are also incumbent candidates, who have won and even won a landslide. For example, the Surabaya City Pilot won by Tri Rismaharini-Wisnu with 86.2%. From the results of this study, researchers can conclude that first, the victory of the incumbent more on social capital factor (second), Bina Desa prorgram, third door to door strategy, fourth, offer environmental, tourism, health, and fifth , regional infrastructure development program. With a good infrastructure is believed to improve the economy that led to the welfare of local communities.DOI: https://doi.org/10.26905/pjiap.v3i1.1644